Limited cardiopulmonary capacity in patients with liver cirrhosis when compared to healthy subjects - Nasser,Igor (2021)
SUMMARY OBJECTIVES: The present study compared cardiorespiratory capacity between cirrhotic patients and healthy subjects. METHODS: Nineteen cirrhotic patients and 19 healthy subjects, paired by age and gender, participated in the study. Volunteers performed an incremental cardiopulmonary test with a ramp protocol, a ventilatory and metabolic variables were obtained and analyzed. The recovery was analyzed by calculating the time needed for 50% of oxygen consumption (VO2) recovery to occur as the median between the peak of the exercise and the end of recovery on the VO2 curve (T1/2). The VE/VCO2 slope were performed by the linear regression of ventilation (VE) and carbon dioxide production (VCO2) data. RESULTS: During resting condition, cirrhotic patients presented significantly higher levels of VO2 compared to healthy subjects. The VE/ VO2 and VE/ VCO2 values were significantly higher in the control group at the anaerobic threshold and at the peak of the test compared to cirrhotic patients. Time under effort was significantly higher for healthy subjects. CONCLUSIONS: Based on these findings, it is possible to conclude that liver cirrhosis can compromise the patients’ quality of life, mainly by inducing metabolic alterations which can impair functional capacity and lead to a sedentary lifestyle.